2006
DOI: 10.1086/499932
|View full text |Cite
|
Sign up to set email alerts
|

Thermal X‐Ray Iron Line Emission from the Galactic Center Black Hole Sagittarius A*

Abstract: We model thermal X-ray emission from the accreting supermassive black hole Sagittarius A Ã at the Galactic center. For the region inside 1B5 of the center, we use a generalized radiatively inefficient accretion flow ( RIAF) model, and for the region out to 10 00 we use published models of the ambient hot gas. We calculate the equivalent widths of hydrogen-like and helium-like emission lines of various elements, notably iron. We predict that a strong helium-like iron line with an equivalent width $1 keV should … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 33 publications
7
90
3
Order By: Relevance
“…Locally, accurate black hole mass measurements have been made for our own Galaxy (e.g., Schödel et al 2003;Ghez et al 2005) and the Andromeda galaxy (e.g., Bender et al 2005). Our own Galactic black hole is rather dormant based on its relatively low X-ray emission (e.g., Baganoff et al 2003;Xu et al 2006), but in general these massive black holes are considered a key component of active galactic nuclei (AGNs), in which accretion onto the black hole itself can produce large amounts of energy efficiently (e.g., Lynden-Bell 1969;Pringle 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Locally, accurate black hole mass measurements have been made for our own Galaxy (e.g., Schödel et al 2003;Ghez et al 2005) and the Andromeda galaxy (e.g., Bender et al 2005). Our own Galactic black hole is rather dormant based on its relatively low X-ray emission (e.g., Baganoff et al 2003;Xu et al 2006), but in general these massive black holes are considered a key component of active galactic nuclei (AGNs), in which accretion onto the black hole itself can produce large amounts of energy efficiently (e.g., Lynden-Bell 1969;Pringle 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Sgr A ⋆ also appears as a faint (L 2−10 keV ∼ 2×10 33 erg s −1 ) X-ray source (Baganoff et al 2003;Xu et al 2006) observed to be extended with a size of about ∼ 1 ′′ . The observed size is comparable to the Bondi radius and the quiescent X-ray emission is thought to be the consequence of material that is captured at a rate of 10 −6 M⊙ yr −1 from the wind of nearby stars (Melia 1992;Quataert 2002;Cuadra et al 2005;.…”
mentioning
confidence: 99%
“…Interestingly, the observed spectrum of the emission resembles that of the surrounding diffuse plasma and shows the Fe Kα line at ∼ 6.6 keV ( Fig. 10d; Wang et al 2006b;Xu et al 2006). Therefore, the flow is also in an NEI state.…”
Section: The Gc Clustermentioning
confidence: 81%